Islam and Politics in Indonesia : Historical Perspective - Qisthi Faradina Ilma Mahanani; Mega Alif Marintan; Irma Ayu Kartika Dewi; Fuadi, Moh Ashif (Al-Isnad: Journal of Islamic Civilization History and Humanities, 2022)
This research explains the dynamic perspective of Islam and politics in Indonesia. The relationship between Islam and the political situation in Indonesia is not always harmonious. With qualitative methods through the study of literature, this research resulted in the conclusion that Islamic and political ndication are two aspects that converge in its development that has never been interrupted from the previous period. The existence of Islam in Indonesia is largely determined by the objective conditions built by the Muslims themselves through qualifications and political capacities that are insightful in the formation of the intellectuality of their people. The condition of Muslims today has indeed progressed, but institutionally politically it has regressed. Therefore, discussing Islamic and political issues is felt increasingly urgently by Muslims themselves. The engineering of the conversation and its implementation includes a doctrinal Understanding of Islam that is contextual to the political growth of the nation, a coaching system that can liberate people from material and spiritual backwardness, and leadership that is not only charismatic, but also dedicative and professional. Keywords: Islam, Politic, Perspective, Historical